Shipwrecked Identities Navigating Race on Nicaragua's Mosquito Coast - Pineda, Baron (Rutgers University Press, 2006)
Global identity politics rest heavily on notions of ethnicity and authenticity. In contemporary Latin America there is a resurgence of indigenous claims for cultural and political autonomy and for the benefits of economic development. Yet these identities have often been taken for granted.In this historical ethnography, Baron Pineda traces the history of the port town of Bilwi, now known officially as Puerto Cabezas, on the Atlantic coast of Nicaragua to explore the development and function of racial categories in this region. In the process, he provides insight into the causes and meaning of social movements and political turmoil. Shipwrecked Identities also includes important critical analysis of the role of anthropologists and other North American scholars in the Contra-Sandinista conflict as well as the ways these scholars have defined ethnic identities in Latin America.